1990
DOI: 10.1161/01.cir.81.1.312
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous atrial septal defect occlusion in piglets with a "buttoned" double-disk device.

Abstract: The feasibility and safety of transvenous closure of atrial septal defects by a new device was tested in 20 piglets, in which atrial septal defects were created by foramen ovale dilatation with angioplasty balloons. The device was small enough to be introduced in a 7F or 8F sheath, and it measured 20-25 mm. It has no hooks and consists of a foam occluder from the left atrium and a counter-occluder from the right atrium, buttoned independently. The animals were observed by angiography and color flow mapping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 4 publications
0
50
0
4
Order By: Relevance
“…28 Bridges et al 29 first proposed that PFO closure would reduce the incidence of recurrent strokes and demonstrated a statistically significant effect of PFO closure on a small group of high-risk patients. Since then, numerous studies have shown that transcatheter PFO closure with current techniques is safe and seems to protect against recurrent strokes in this patient population.…”
Section: Catheter-based Pfo Closuresmentioning
confidence: 99%
“…28 Bridges et al 29 first proposed that PFO closure would reduce the incidence of recurrent strokes and demonstrated a statistically significant effect of PFO closure on a small group of high-risk patients. Since then, numerous studies have shown that transcatheter PFO closure with current techniques is safe and seems to protect against recurrent strokes in this patient population.…”
Section: Catheter-based Pfo Closuresmentioning
confidence: 99%
“…However, the procedure has not yet achieved widespread clinical use and is still investigational. Previous devices include the clamshell septal occluders [3,4], Sideris prosthesis (buttoned device) [5][6][7], the atrial septal defect occlusion system (ASDOS) [8,9], the Das Angel Wing [10,11] and the Pavenik monodisc [12]. All these were bulky devices, requiring larger sheaths for introduction which make their application difficult in small children.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to surgery, a variety of devices for transcatheter closure of ASDs have been developed over the past 25 years, but none has gained wide acceptance. Large delivery sheaths, cumbersome implantation techniques, inability to recapture, structural failure, dislodgement and embolization of the device are some of the limitations of previously prescribed techniques [2][3][4][5][6][7][8][9][10][11][12]. This study describes our experience with transcatheter closure of ASDs and PDAs using a new self expanding, self-centering and repositionable device, the Amplatzer.…”
Section: Introductionmentioning
confidence: 99%
“…The buttoned device was successfully implanted in 17 (85%) of 20 attempts. The failures were in the first three animals; presumably related inexperience of the operator and design imperfections (Sideris et al, 1990a). Full occlusion of the ASD and endothelialization of the device was demonstrated in all the 17 successful implantations.…”
Section: Buttoned Devicementioning
confidence: 95%